Pandangan Pemikir Ekonomi Islam Mengenai Riba Perspektif Al-Ghazali dan Al-Maududi - Widi Lailatul Fajar; Syifa Syafiatul Huda; Elga Achmad Firdaus; Lina Marlina (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
The existence of usury is a practice that is strictly prohibited, especially in economic activities. The prohibition is not without reason, but there are many negative impacts that will arise from the practice of usury which has been clearly explained in the Qur'an regarding its prohibition. The purpose of this study is to find out and present the concept of economic thought put forward by Imam Al-Ghazali and Abu A'la Al-Maududi, especially regarding the views of each figure on the practice of usury. The method used in this research is by studying literature obtained from various books and journals. Al-Ghazali's view of usury is that usury is a form of deviation from the function of money which should only be used as a medium of exchange, not as a commodity that can be traded. As for Al-Maududi's view that in order to realize an Islamic economy, all forms of usury practices must be eliminated. Both figures have the same view that the practice of usury is a form of human moral decline in the form of excessive greed and love of wealth so that they do not care about other humans.